Effects of electromagnetic fields emitted from W‐CDMA‐like mobile phones on sleep in humans. Issue 8 (22nd August 2013) - Nakatani‐Enomoto, Setsu; Furubayashi, Toshiaki; Ushiyama, Akira; Groiss, Stefan Jun; Ueshima, Kazumune; Sokejima, Shigeru; Simba, Ally Y.; Wake, Kanako; Watanabe, So‐ichi; Nishikawa, Masami; Miyawaki, Kaori; Taki, Masao; et al.
ABSTRACT In this study, we investigated subjective and objective effects of mobile phones using a Wideband Code Division Multiple Access (W‐CDMA)‐like system on human sleep. Subjects were 19 volunteers. Real or sham electromagnetic field (EMF) exposures for 3 h were performed before their usual sleep time on 3 consecutive days. They were exposed to real EMF on the second or third experimental day in a double‐blind design. Sleepiness and sleep insufficiency were evaluated the next morning. Polysomnograms were recorded for analyses of the sleep variables and power spectra of electroencephalograms (EEG). No significant differences were observed between the two conditions in subjective feelings. Sleep parameters including sleep stage percentages and EEG power spectra did not differ significantly between real and sham exposures. We conclude that continuous wave EMF exposure for 3 h from a W‐CDMA‐like system has no detectable effects on human sleep. Bioelectromagnetics 34:589–598, 2013. © 2013 Wiley Periodicals, Inc.